2019
DOI: 10.3390/s19194302
|View full text |Cite
|
Sign up to set email alerts
|

Single-Baseline RTK Positioning Using Dual-Frequency GNSS Receivers Inside Smartphones

Abstract: Global Navigation Satellite System (GNSS) positioning is currently a common practice thanks to the development of mobile devices such as smartphones and tablets. The possibility to obtain raw GNSS measurements, such as pseudoranges and carrier-phase, from these instruments has opened new windows towards precise positioning using smart devices. This work aims to demonstrate the positioning performances in the case of a typical single-base Real-Time Kinematic (RTK) positioning while considering two different kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 19 publications
0
33
0
1
Order By: Relevance
“…Однако, получаемая точность недостаточна для движения автономных автомобилей в городе, поскольку в лучшем случае GNSS достигает метровой точности, в то время как автономное вождение требует точности определения местоположения до 5-10 сантиметров. В таком случае используют технологию RTKпоправок [12], которые позволяют достичь требуемой точности. Однако, в чистом виде GNSS RTK плохо подходит для движения в городских условиях из-за большого количества зон, где сигнал не может быть принят, например, в тоннеле или при движении в условиях плотной застройки.…”
Section: Hd-карты и система локализацииunclassified
“…Однако, получаемая точность недостаточна для движения автономных автомобилей в городе, поскольку в лучшем случае GNSS достигает метровой точности, в то время как автономное вождение требует точности определения местоположения до 5-10 сантиметров. В таком случае используют технологию RTKпоправок [12], которые позволяют достичь требуемой точности. Однако, в чистом виде GNSS RTK плохо подходит для движения в городских условиях из-за большого количества зон, где сигнал не может быть принят, например, в тоннеле или при движении в условиях плотной застройки.…”
Section: Hd-карты и система локализацииunclassified
“…Location Based Services (LBS) is a basic service that obtains the current location and provides information resources through various mobile location technologies [1]- [3]. At present, the most basic localization technology generally uses GPS sensors for real-time localization, but GPS signals are easily blocked, or interfered, thus high-precision localization cannot be realized [4]- [6]. Therefore, based on a single data source, many research institutions, universities, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In later Android versions, it was possible to turn off the duty cycling mode, making the observables applicable for phase-based positioning methods. Based on this, first single-baseline RTK positioning experiments considering two different kinds of multi-frequency and multi-constellation master stations took place [16]. This research work demonstrated that it is not possible to fix phase ambiguities and therefore to reach cm-accuracy in real-time, mostly due to the low quality of GNSS raw measurements collected by a mobile phone.…”
Section: Introductionmentioning
confidence: 99%